Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_si.2020.sm3p.3
|View full text |Cite
|
Sign up to set email alerts
|

Mode-selective frequency conversion in a three-mode fiber

Abstract: We present a scheme for spatial-mode-selective frequency conversion in a few-mode fiber and experimentally demonstrate upconversion of either of two signal modes from C-band to fundamental mode in S-band with crosstalk below -15.5 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Compared to PPLN platform, nonlinear FMFs can offer wider design options for mode-and dispersion-engineering and better mode match to the FMFs used in transmission links. Our results have shown good crosstalk performance (mode selectivity) for each of the two IM-FWM processes [21,22] and demonstrated their combined ability to selectively convert any mode superposition in either (LP01, LP11a) [22][23][24] or orbital-angular-momentum-compatible (LP11a, LP11b) [24,25] two-mode signal space.…”
Section: Spatial-mode-selective Quantum Frequency Conversionmentioning
confidence: 70%
See 1 more Smart Citation
“…Compared to PPLN platform, nonlinear FMFs can offer wider design options for mode-and dispersion-engineering and better mode match to the FMFs used in transmission links. Our results have shown good crosstalk performance (mode selectivity) for each of the two IM-FWM processes [21,22] and demonstrated their combined ability to selectively convert any mode superposition in either (LP01, LP11a) [22][23][24] or orbital-angular-momentum-compatible (LP11a, LP11b) [24,25] two-mode signal space.…”
Section: Spatial-mode-selective Quantum Frequency Conversionmentioning
confidence: 70%
“…More recently, we have developed a scheme of similar functionality (mode demultiplexing by mode-selective frequency conversion) in a third-order nonlinear medium (FMF). Based on our previous studies of Kerr [16][17][18][19] and Raman [20] nonlinearities in FMFs, we have identified a combination of two inter-modal four-wave mixing (IM-FWM) processes [21] that can realize the spatial-mode-selective frequency conversion. Compared to PPLN platform, nonlinear FMFs can offer wider design options for mode-and dispersion-engineering and better mode match to the FMFs used in transmission links.…”
Section: Spatial-mode-selective Quantum Frequency Conversionmentioning
confidence: 99%